Optical backscatter in flume experiments measured during Changing Arctic Ocean cruises JR17007 and JR18006 in the Barents Sea. - Ruhl, Saskia (British Oceanographic Data Centre, National Oceanography Centre, NERC, UK, 2020)
Optical backscatter measured within annular flume channels, using OBS-1B optical backscatter sensors from D&A Instruments. Measurements were made during a ship-board sampling campaign in the Barents Sea along a North-South transect at 30° Longitude in July 2018 (cruise JR17007) and July 2019 (cruise JR18006) as part of the Changing Arctic Ocean programme.